Detecting Ionospheric Precursors of a Deep Earthquake (378.8 km) on 7 July 2013, M w=7.2, in Papua New Guinea under a Geomagnetic Storm: Two-Dimensional Principal Component Analysis - Jyh-Woei Lin (Earth Sciences Research Journal)
Two-dimensional ionospheric total electron content (TEC) data were collected during the time period from 00:00 on 2 July to 12:00 UT on 08 July 2013. This period spanned 5 days before to 1 day after a deep earthquake (378.8 km) in Papua New Guinea at 18:35:30 on 7 July 2013 UT (Mw=7.2). Data were examined by two-dimensional principal component analysis (2DPCA) to detect TEC precursors related to the earthquake because TEC precursors have usually appeared in earlier time periods (Liu et al. 2006). A TEC precursor was highly localized around the epicenter on 6 July for 5 minutes, from 06:00 to 06:05. Ionizing radiation from radon gas release could possibly have caused the anomalous TEC fluctuation through, for example, a density variance. The plasma might have experienced large damping to cause short-term TEC fluctuations, and the gas released in a small amount in a short time period. 2DPCA can also identify short-term TEC fluctuations, but this fluctuation lasted for a considerable length of time. Other background TEC anomalies caused by the geomagnetic storm, small earthquakes and non-earthquake activities, e.g., equatorial ionization anomaly (EIA), resulted in small principal eigenvalues. Therefore, the detection of TEC precursors through large eigenvalues was not due to these background TEC anomalies.